Role of urinary transforming growth factor beta-b1 and monocyte chemotactic protein-1 as prognostic biomarkers in posterior urethral valve - Pranay Panigrahi; Sarita Chowdhary; Shyamendra Pratap Sharma; Rakesh Kumar; Neeraj Agarwal; Shiv Prasad Sharma (Wolters Kluwer Medknow Publications, 2020)
Background: Posterior Urethral Valves (PUV) are the most common cause of congenital LUT obstruction in males. Biomarkers of glomerular or tubular injury may be of particular value in predicting the need for surgical intervention or in tracing progression of chronic kidney disease. Measurement of biomarker in urine is relatively easy. Aim: To evaluate the changes in values of urinary Transforming Growth Factor Beta 1(TGF-B1) and Monocyte Chemotactic Protein (MCP-1) before and after valve ablation and its prognostic value in Posterior urethral valve. Material and Method: This prospective study was conducted from September 2016 to August 2018. The study group included 20 consecutive male babies with the diagnosis of PUV treated and followed up versus equal numbers of age matched control without any renal or urinary tract disease. Pre-operative urine samples were collected in Operative room. Cystoscopy and valve ablation was done. Follow up was done clinically by urinary stream and radiologically with VCUG. Follow-up was planned at 1 month, 3 months and 6 months following cystoscopic valve ablation. All collected urine samples were centrifuged at 10,000 rpm for 20 minutes. Supernatant was collected and two divided aliquots were stored at -200c to be thawed on the day of assay. Optical density of each well was recorded at 450 nm and 540 nm A p-value of <0.05 was considered to be statistically significant. Result and Discussion: Out of 20 cases of PUV, 14 (70%) cases were 1st born males of their family. The median age at the time of valve ablation in PUV cases was 2.5 (1.20-3.87) years.. Most common symptoms are fever and UTI. The preoperative median serum creatinine level was 1.65 mg/dl(1.22-2.42) pre-ablation, and fall significantly after ablation. Median eGFR level (calculated) was 25.635 (16.38-35.40) and after 6 months was 71.490 (45.44-96.93). Preoperative median MCP1 in PUV cases was 147.2 (82.8-512.5) and significant difference was also found in 1st, 3rd and 6th months after surgery (p<0.001, p=0.004 and p=0.002).Preoperative median TGF-B1 level was 197.8 pg/ml (79.9-386.4). There was no statistically significant change in TGF-B1 level at preoperative to 1 month and preop to 3 months after surgery but at 6 months after surgery the median TGF-B1 level significantly decreased as compared with preoperative TGF-B1 level. Conclusion: TGF β1 and MCP1 can be considered as prognostic urinary biomarkers in patients of PUV and can be used to specify and counsel patient's attendant regarding possibility of ESRD and need for further intervention.